Corticostriatal-limbic correlates of sub-clinical obsessive-compulsive traits. (30th March 2019) - Kubota, Yasutaka; Sato, Wataru; Kochiyama, Takanori; Uono, Shota; Yoshimura, Sayaka; Sawada, Reiko; Toichi, Motomi
Highlights: Obsessive-compulsive traits (OCTs) are frequent in general population (5%–13%). This is the first voxel-based morphometry (VBM) to investigate volume changes of the corticostriatal-limbic structures related to OCTs. Volume changes associated with OCTs were identified in the left putamen and the left amygdala. The structural covariance analysis highlighted increased covariances in relation to OCTs between the left putamen to bilateral medial prefrontal cortex and to the left cerebellum, and between the left globus pallidus to the bilateral anterior cingulate cortices. These structural changes in the corticostriatal-limbic circuitries may reflect "neuronal obsessive traits" that might precondition OCD at the network level. Abstract: Obsessive-compulsive (OC) traits such as intrusive worrisome ideas or excessive concerns for threats are frequent in general population (5%–13%). However, the structural neural correlates of the sub-clinical OC traits remain largely unknown. Based on the data of obsessive-compulsive disorder (OCD), we hypothesized that the subcortical and cortical structures, constituting the cortico-striatal-thalamo-cortical circuit (CSTC) and the limbic system, could be associated with OC traits. Here we conducted voxel-based morphometry (VBM) in order to investigate fine grained volume changes of these structures in 49 non-clinical subjects. Analysis of structural covariances of these structures was also conducted. We identified volume changes associated with OC traits in the left putamen and the left amygdala. The results of structural covariance analysis revealed increased covariances in relation to the heightened OC traits between the left putamen to bilateral medial prefrontal cortex and to the left cerebellum, and between the left globus pallidus to the bilateral anterior cingulate cortices. The present finding of volume changes of the corticostriatal-limbic structures may reflect neuroplasticity associated with OC traits. Since the abnormality of these structures were also observed in the clinical OCD, the subclinical subjects with OC traits shared "neuronal obsessive traits" that might precondition OCD at the network level.